2019
DOI: 10.1002/anie.201905389
|View full text |Cite
|
Sign up to set email alerts
|

A Triangular Platinum(II) Multinuclear Complex with Cytotoxicity Towards Breast Cancer Stem Cells

Abstract: The preparation of multinuclear metal complexes offers ar oute to novel anticancer agents and delivery systems. The potency of an ovel triangular multinuclear complex containing three platinum atoms, Pt-3,t owards breast cancer stem cells (CSCs) is reported. The trinuclear platinum(II) complex, Pt-3 exhibits selective toxicity towards breast CSCs over bulk breast cancer cells and non-tumorigenic breast cells. Remarkably, Pt-3 inhibits the formation, size, and viability of mammospheres to ab etter extent than s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 62 publications
1
48
0
Order By: Relevance
“…Notably, the mammosphere potency of 1 and 3 was much lower than salinomycin, cisplatin, and the corresponding copper(II) complex with naproxen, Cu‐1 under identical conditions (Table 1). [8b, 16, 18] Previous reports and control experiments conducted in this study showed that NiCl 2 ⋅6 H 2 O, naproxen, and indomethacin were all non‐toxic towards mammospheres (IC 50 >133 μ m , Figure S18 and Table 1). [8a] Therefore the mammosphere potency observed for 1 and 3 is likely to be due to the intact mammosphere uptake of the nickel(II) complexes, which facilitates the concerted co‐delivery of all the complex components.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Notably, the mammosphere potency of 1 and 3 was much lower than salinomycin, cisplatin, and the corresponding copper(II) complex with naproxen, Cu‐1 under identical conditions (Table 1). [8b, 16, 18] Previous reports and control experiments conducted in this study showed that NiCl 2 ⋅6 H 2 O, naproxen, and indomethacin were all non‐toxic towards mammospheres (IC 50 >133 μ m , Figure S18 and Table 1). [8a] Therefore the mammosphere potency observed for 1 and 3 is likely to be due to the intact mammosphere uptake of the nickel(II) complexes, which facilitates the concerted co‐delivery of all the complex components.…”
Section: Resultsmentioning
confidence: 63%
“…The corresponding copper(II) complex with indomethacin, Cu‐3 (see Figure S13 for chemical structure) preferentially killed HMLER cells over HMLER‐shEcad cells [8b] . Strikingly, the indomethacin‐containing nickel(II) complex, 3 displayed 2.3‐fold ( p <0.05, n =12) and 3.1‐fold ( p <0.05, n =12) greater potency for CSC‐enriched HMLER‐shEcad cells than salinomycin and cisplatin (a platinum‐based anticancer agent), respectively [8a, 16] . The NSAIDs components, naproxen and indomethacin were previously shown to be non‐toxic towards both HMLER and HMLER‐shEcad cells (IC 50 values >100 μ m ) under identical conditions [8a, b] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, the IC 50 value for 4 (0.54 � 0.01 μM) was 34 and 25 times lower than that reported for salinomycin and cisplatin, respectively, under identical conditions. [17,21] [Cu(L 1 )Cl] displayed significantly (p < 0.05) lower potency for HMLER-shEcad spheroids than 1-4, ( Figure S17, Table 1) indicating that the intact copper(II) complexes containing both the Schiff base, L 1 and the corresponding polypyridyl ligand are responsible for the observed activities with HMLER-shEcad spheroids. The addition of the most potent copper(II) complex, 4 (IC value for 5 days) to single cell suspensions of nontumorigenic breast epithelial MCF10 A cells did not significantly (p = 0.20) change the number or size of MCF10 A spheroids formed ( Figure 3A and C).…”
Section: Resultsmentioning
confidence: 99%
“…The most potent complex within the series, 4 displayed 13‐fold and 18‐fold greater potency ( p <0.05, n=18) for CSC‐enriched HMLER‐shEcad cells than salinomycin and cisplatin, respectively (Table 1). [16a,21] Control studies showed that [Cu( L 1 )Cl] was nontoxic towards HMLER and HMLER‐shEcad cells (IC 50 >100 μM), indicating that the cytotoxicity of 1 – 4 towards bulk breast cancer cells and breast CSCs is likely to result from the intact copper(II) complexes, containing both the Schiff base, L 1 and the corresponding polypyridyl ligand (Figure S13, Table 1).…”
Section: Resultsmentioning
confidence: 99%